Psychometric testing of the Indonesian version of the Nurses’ Ethical Behavior in Protecting Patients’ Rights (I-NEBPPR) scale - Dian Susmairni; Do Thi Ninh; Cheng Li; GunJeong Lee (Belitung Nursing Journal, 2023)
Background: Nurses routinely encounter ethical dilemmas with patients and healthcare professionals. Therefore, it is crucial for them to be conscious of ethical principles and apply them in their decision-making processes. However, no specific questionnaire is available to assess nurses’ ethical conduct in Indonesia. Objective: This study aimed to assess the psychometric properties of the Indonesian version of the Nurses’ Ethical Behavior in Protecting Patients’ Rights (I-NEBPPR) scale. Methods: Following the World Health Organization’s guidelines and utilizing the WHODAS 2.0 translation package, the NEBPPR was translated into Bahasa Indonesia and underwent a rigorous translation and adaptation process. Data were collected between October and November 2022 and included 283 Indonesian nurses as participants. Confirmatory factor analysis (CFA) was used to evaluate construct validity. Convergent validity, discriminant validity, and reliability were also performed for comprehensive evaluation. IBM SPSS statistics version 27.0 and AMOS 24.0 were used for statistical analysis. Results: Five items were excluded from the original versions, forming five subscales that include a combined total of 23 items. The subscales are as follows: Factor 1 (Respect for right to information and decision), Factor 2 (Providing fair care), Factor 3 (Providing benefit-not harming), Factor 4 (Respect for patient values and choices), and Factor 5 (Attention to privacy). The I-NEBPPR model demonstrated robust construct validity with factor loadings ranging from 0.453 to 0.871. CFA showed satisfactory model fit indices (χ2/df = 1.554 (p <0.001), GFI = 0.906, CFI = 0.929, IFI = 0.930, RMSEA = 0.044). Reliability metrics were solid, with a Cronbach’s alpha of 0.819 and composite reliability exceeding 0.6. Both convergent validity, as indicated by AVE, and discriminant validity, as confirmed by the Fornell-Larcker criterion, met established thresholds. Conclusion: It is affirmed that the 23-item I-NEBPPR demonstrated strong psychometric properties, making it a valuable, practical, and time-efficient tool for nurse supervisors, nurse managers, and nurse leaders to assess nurses’ clinically-based ethical behavior in their efforts to protect patient’s rights.